Rhymes with fighter : Clayton Yeutter, American statesman - Weber, Joseph (Professor of journalism) (University of Nebraska Press, 2021)
"This biography tells the life story of Nebraska native Clayton Yeutter (1930-2017), whose accomplishments in international trade, agriculture, and economics are still very prominent in today's world"--